2008
DOI: 10.1111/j.1471-3802.2008.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental co‐ordination disorder (DCD) in adolescents and adults in further and higher education

Abstract: Few studies have looked at the strengths and weaknesses and needs of students with developmenal co‐ordination disorder (DCD). This paper describes a cohort of 93 UK students currently studying at further or higher education and who have reported motor difficulties present since childhood. The study group consisted of 21 reporting to have DCD only, 38 with DCD plus another diagnosis (a combination of any of the following: dyslexia, attention deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 28 publications
(34 reference statements)
3
85
0
11
Order By: Relevance
“…Cantell, Smyth, & Ahonen, 2003;Hall, 1988). Nicméně následné studie (viz přehled Cantell & Kooistra, 2002), a jiné práce (Cantell et al, 2003;Kirby, Sugden, Beveridge, & Edwards, 2008) poskytly důkazy o přetrvávání obtíží v motorické koordinaci až do střední a pozdní adolescence se 32-87% pravděpodobností. Je zřejmé, že vývoj DCD je značně variabilní a může přetrvávat do adolescence a dospělosti (Cousins & Smyth, 2003;Kirby et al, 2008;Missiuna, Moll, King, Stewart, & Macdonald, 2008).…”
Section: úVodunclassified
See 2 more Smart Citations
“…Cantell, Smyth, & Ahonen, 2003;Hall, 1988). Nicméně následné studie (viz přehled Cantell & Kooistra, 2002), a jiné práce (Cantell et al, 2003;Kirby, Sugden, Beveridge, & Edwards, 2008) poskytly důkazy o přetrvávání obtíží v motorické koordinaci až do střední a pozdní adolescence se 32-87% pravděpodobností. Je zřejmé, že vývoj DCD je značně variabilní a může přetrvávat do adolescence a dospělosti (Cousins & Smyth, 2003;Kirby et al, 2008;Missiuna, Moll, King, Stewart, & Macdonald, 2008).…”
Section: úVodunclassified
“…Navzdory možným kompenzacím zhoršených pohybových dovedností byl u adolescentů a mladých dospělých pozorován horší výkon v úlohách, které vyžadují jemnou a hrubou vizuomotorickou koordinaci jako je řízení auta, psaní, chytání předmětů a konstrukční úlohy (Cousins & Smyth, 2003;Kirby et al, 2008;Missiuna et al, 2008). U jedinců těchto věkových období byly rovněž zjištěny problémy s udržením zaměstnání, ačkoli měli akademické vzdělání, problémy v sociální interakci a obtíže v exekutivních funkcích (Cousins & Smyth, 2003;Kirby, Edwards, & Sugden, 2011;Kirby et al, 2008).…”
Section: úVodunclassified
See 1 more Smart Citation
“…Functionally, individuals with DCD or developmental dyspraxia have trouble coordinating their movements to learn new fine and gross motor tasks required to perform instrumental daily activities, such as tying shoelaces, dressing, handwriting, playing sports, and using playground equipment [1,3,12,13]. In addition, decreased educational performance and poor social emotional adjustment, perhaps a result of participation limitations, have been found in children, adolescents, and adults with developmental coordination disorders [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although DCD is most apparent in childhood when many new skills are acquired and motor milestones are tracked, an increasing body of evidence reveals that many with the disorder continue to have difficulties with coordination and have reduced participation in motor tasks during adolescence and adulthood [15][16][17][26][27][28][29]. In a longitudinal study of children with DCD beginning when the children were 5 years old, Cantell, Smyth, and Ahonen [26] found that a subset of participants with relatively more severe motor impairments compared to other participants continued to have motor difficulties at age 17.…”
Section: Introductionmentioning
confidence: 99%